Comparison of variants in TPMT and NUDT15 between sequencing and genotyping methods in a multistate pediatric institution - Kelsey J. Cook; Victoria Grusauskas; Lucy Gloe; Benjamin Q. Duong; Renee C. Gresh; E. Anders Kolb; Manisha Bansal; Allison S. Bechtel; Ramamoorthy Nagasubramanian; Susan M. Kirwin; Kathryn V. Blake; Nathan D. Seligson (Wiley, 2023)
Abstract The risk of severe adverse events related to thiopurine therapy can be reduced by personalizing dosing based on TPMT and NUDT15 genetic polymorphisms. However, the optimal genetic testing platform has not yet been established. In this study, we report on the TPMT and NUDT15 genotypes and phenotypes generated from 320 patients from a multicenter pediatric healthcare system using both Sanger sequencing and polymerase chain reaction genotyping (hereafter: genotyping) methods to determine the appropriateness of genotyping in our patient population. Sanger sequencing identified variant TPMT alleles including *3A (8, 3.2% of alleles), *3C (4, 1.6%), and *2 (1, 0.4%), and NUDT15 alleles including *2 (5, 3.6%) and *3 (1, 0.7%). For genotyped patients, variants identified in TPMT included *3A (12, 3.1%), *3C (4, 1%), *2 (2, 0.5%), and *8 (1, 0.25%), whereas NUDT15 included *4 (2, 1.9%) and *2 or *3 (1, 1%). Between Sanger sequencing and genotyping, no significant difference in allele, genotype, or phenotype frequency was identified for either TPMT or NUDT15. All patients who were tested using Sanger sequencing would have been accurately phenotyped for either TPMT (124/124), NUDT15 (69/69), or both genes (68/68) if they were assayed using the genotyping method. Considering 193 total TPMT and NUDT15 Sanger Sequencing tests reviewed, all tests would have resulted in an appropriate clinical recommendation if the test had instead been conducted using the comparison genotyping platforms. These results suggest that, in this study population, genotyping would be sufficient to provide accurate phenotype calls and clinical recommendations.